Eastern European migration to Portugal: from an unexpected migration to an uncertain future - Marques, José Carlos (2018)
In Portugal, Eastern European immigrants only become numerically significant at the end of the 1990s. Until that time, the Portuguese immigration landscape was mainly characterized by the presence of citizens from former Portuguese colonies in Africa and from Brazil. The study of this phenomenon is particularly interesting because it allows to analyse the constitution and development of a new immigration flow and of new immigrant communities in the country and, since the 2008 crisis, to investigate the strategies that immigrants use to face an economic situation that seems to hinder the fulfilment of their initial motivations for migration. Considering the importance of economic motives, it should be expected that, if the reason that justified migration can no longer be satisfied in Portugal,migrants would adopt strategies to attain their economic wellbeing elsewhere. By focusing on the possibilities that migrants consider when planning their future trajectories in a context marked by an economic downturn, this analysis intends to shed light on some of the factors that could impact on these possibilities. It will be shown that these are not limited by the dichotomy of staying or returning, but are spread over a continuum of mobility options in-between the two extreme options (staying or returning). The objective of this article is twofold. First, it presents the evolution of immigration in Portugal giving special attention to the inflow of Eastern European immigrants at the beginning of the twenty-first century. Second, it intends to analyse the effects of the 2008 economic crisis on this immigration flow and the various options that immigrants could follow in their response to a downturn in the economic situation.